Traditional and medicinal use of Barbaloin: potential for the management of various diseases - Singh, Navdeep; Goyal, Kamya; Sondhi, Shivi; Jindal, Shammy (Journal of Applied Pharmaceutical Research, 2020)
Barbaloin is the phytoconstituent which is obtained from the plant known as aloe vera.  As we all know aloe vera is the main curative medicinal plants, has been traditionally used as alternative treatment against the many skin diseases. Barbaloin extracted from the aloe vera plant which is physically light yellow colored powder. Extraction of barbaloin from the plant Aloe barbadensis Miller had been accomplished by the Soxhelt extraction, Batch extraction experiment and Ultrasound assisted extraction method (UAE). Barbaloin showed various kinds of therapeutic and medicinal properties like anti-diabetic, antioxidants, anti-cancer, anti-inflammatory and and anti-microbial. It also has good effect on cardiovascular system, test perception, enzyme or metabolism and bioavailability. Our Skin plays an important role in the development of skin diseases because there are many types of skin disorders are developed and the variety of disorders may result to dermatitis or they affect the social wellbeing of a person. Due to their good pharmacological activities, Barbaloin have great potential to treat the different type of skin disorders like Eczema, Psoriasis, Burns and wound, Acne, Dandruff, Frostbite, Rashes, Cold sores, Razor burn and Sunburn. To access the effective use of barbaloin there are various attempts have been experimented on the subject of their Pharmacological activities to check their effect on skin disease and the steps regarding the Isolation of barbaloin also has been made. We can examine their effects on chronic skin diseases. In this review article we discuss about the potential of barbaloin on skin disorders, medicinal importance or Pharmacological activities and their methods of extraction.